The Effect of Risk Investment, Financial Statement Understanding, and Financial Literacy on Students’ Investment Interest - Anthony Holly; Ana Mardiana; Robert Jao; Marselinus Asri; George Phieter Theovanus (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: The purpose of this study is to investigate the effect of investment risk on students' interest in investing in stocks, the effect of financial statement understanding on students' interest in investing in stocks, and the effect of financial literacy on students' interest in investing in stocks. Method: The research design using quantitative methods, which data collection method is documentation, and using multiple regression analysis technique. Sample of the research is students from Atma Jaya university from accounting study program entrance year 2021 and 2022. Data collection using googl form. Sample size is 147 respondents. Findings: The results of the study show that investment risk has a positive and significant effect on students’ interest in investing in stocks, financial statement comprehension has a positive but not significant effect on students’ interest in investing in stocks, and financial literacy has a positive and significant effect on investing interest. Implications: the gen z has motivation of investing if they have the knowledge about the investing activities which can reduce risk in investing.